Application of Interactive Learning Methods and Character Strengthening in Aisyiyah Penatarsewu Kindergarten : Penerapan Metode Pembelajaran Interaktif dan Penguatan Karakter di TK Aisyiyah Penatarsewu (Indonesian Journal of Cultural and Community Development, 2024)
This research aims to explore the role of Real Work Lecture (KKN) students in supporting learning activities at the Aisyiyah Kindergarten in Penatarsewu Village and their contribution in increasing awareness of children's dental health. Using a qualitative descriptive approach, this research assesses the impact of KKN on educational learning, social and cultural introduction, and children's health. The research results show that KKN students have succeeded in applying creative and innovative methods, introducing local social and cultural values, and increasing children's understanding of dental health, including the importance of limiting consumption of sweet foods. The involvement of KKN students makes a significant contribution to improving the quality of education, social knowledge, culture and children's health. This program shows the potential for synergy between higher education and local communities in creating sustainable positive change.